2019
DOI: 10.1073/pnas.1900287116
|View full text |Cite
|
Sign up to set email alerts
|

Engineering energetically efficient transport of dicarboxylic acids in yeast Saccharomyces cerevisiae

Abstract: Biobased C4-dicarboxylic acids are attractive sustainable precursors for polymers and other materials. Commercial scale production of these acids at high titers requires efficient secretion by cell factories. In this study, we characterized 7 dicarboxylic acid transporters in Xenopus oocytes and in Saccharomyces cerevisiae engineered for dicarboxylic acid production. Among the tested transporters, the Mae1(p) from Schizosaccharomyces pombe had the highest activity toward succinic, malic, and fumaric acids and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 49 publications
0
54
0
Order By: Relevance
“…The structure of TMDs and NBDs determine the specificity and efficiency of ABC transporter, which can be redesigned to improve the substrate specificity and transport activity, respectively. From the perspective of cellular economics, the energy-independent or less energy-dependent transporter may be the desired protein for product efflux [43]. In this sense, Snq2p may be the most suitable endogenous transporter for modification in future work because it can secret more β-carotene when consuming the same amount of ATP.…”
Section: Acetate Supplementation Enhances the β-Carotene Secretion Inmentioning
confidence: 99%
“…The structure of TMDs and NBDs determine the specificity and efficiency of ABC transporter, which can be redesigned to improve the substrate specificity and transport activity, respectively. From the perspective of cellular economics, the energy-independent or less energy-dependent transporter may be the desired protein for product efflux [43]. In this sense, Snq2p may be the most suitable endogenous transporter for modification in future work because it can secret more β-carotene when consuming the same amount of ATP.…”
Section: Acetate Supplementation Enhances the β-Carotene Secretion Inmentioning
confidence: 99%
“…This transporter has been proven to increase malic acid titer significantly in S. cerevisiae (Zelle et al, 2008). We also recently showed that SpMae1 transporter is likely a SLAC1 voltage-dependent anion channel and is thus very energetically efficient (Darbani et al, 2019). Hence, we expressed transporter gene SpMae1 in Δ ACH1 ST8218, to obtain strain ST8413.…”
Section: Resultsmentioning
confidence: 89%
“…In closing, the use of proton-dependent glucose import by B. bruxellensis may appear expensive from an energetics perspective when compared to the other members of the SLC2 family identified as facilitators (Darbani, Kell and Borodina 2018; Marques et al 2018; Darbani et al 2019). However, this property gives this yeast a competitive edge in nutrient poor environments.…”
Section: Resultsmentioning
confidence: 99%